2022
DOI: 10.1016/j.gore.2021.100918
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the incidence and clinical significance of WT-1 expression in uterine serous carcinoma

Abstract: Highlights Approximately one-fifth of uterine serous carcinomas (USC) will express WT-1. WT-1 expression is associated with a significant improvement in platinum sensitivity. Improved platinum sensitivity among WT-1 positive tumors contributes to a superior PFS vs. WT-1 negative tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
0
5
0
1
Order By: Relevance
“…This marker is therefore considered to be of some value in distinguishing ESC from tubo-ovarian HGSC, particularly if the pattern of expression (negative/focal and weak vs diffuse and strong) is taken into account rather than the presence of any expression. WT1 expression has been shown to have adverse prognostic significance in gynecological cancers overall as it is a marker of tubo-ovarian HGSC, among the most aggressive of all gynecological malignancies 44,45 . Among tubo-ovarian HGSC and ESC, however, expression of WT1 indicates favorable prognosis and improved response to chemotherapy, respectively 43 .…”
Section: Case Presentationmentioning
confidence: 99%
See 3 more Smart Citations
“…This marker is therefore considered to be of some value in distinguishing ESC from tubo-ovarian HGSC, particularly if the pattern of expression (negative/focal and weak vs diffuse and strong) is taken into account rather than the presence of any expression. WT1 expression has been shown to have adverse prognostic significance in gynecological cancers overall as it is a marker of tubo-ovarian HGSC, among the most aggressive of all gynecological malignancies 44,45 . Among tubo-ovarian HGSC and ESC, however, expression of WT1 indicates favorable prognosis and improved response to chemotherapy, respectively 43 .…”
Section: Case Presentationmentioning
confidence: 99%
“…WT1 expression has been shown to have adverse prognostic significance in gynecological cancers overall as it is a marker of tubo-ovarian HGSC, among the most aggressive of all gynecological malignancies. 44,45 Among tubo-ovarian HGSC and ESC, however, expression of WT1 indicates favorable prognosis and improved response to chemotherapy, respectively. 43 This marker is also emerging as a potential antigen target for cancer immunotherapy.…”
Section: High-grade Serous Carcinoma With Concurrent Involvement Of T...mentioning
confidence: 99%
See 2 more Smart Citations
“…Endometrial serous carcinoma is usually negative or only focally positive for WT-1, while adnexal/ extra-uterine HGSC generally demonstrate strong and diffuse WT-1 nuclear staining (Fig. 8) (although it has been reported that up to 20% of extra-uterine HGSC can be negative for WT-1) [32,33]. In these cases, clinical and radiologic correlation can be recommended in the diagnostic comment.…”
Section: Ovarian Epithelial Neoplasmsmentioning
confidence: 99%